2012
DOI: 10.1111/j.1365-2125.2012.04285.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of enoxaparin in critically ill patients with normal renal function

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Venous thromboembolism is a frequent complication in critically ill patients that has a negative impact on patient outcomes. • Critically ill patients have significantly lower plasma anti‐factor‐Xa activity levels compared with control patients after administration of subcutaneous heparin. • The clinical relevance of the different anti‐factor‐Xa levels after prophylactic doses of low molecular weight heparin (LMWH) in critically ill patients is not completely understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
4
10
2
1
Order By: Relevance
“…Our study reinforces the findings from a variety of clinical settings that LMWH prophylaxis reduces the proportion of patients with a significant bleeding event when compared with UFH and has a reduced rate of HIT . The significant reduction in bleeding may be because of the more consistent pharmacokinetic and dynamic properties demonstrated by LMWHs when compared with UFH . Our secondary analysis showed approximately a 2% significant reduction in significant bleeding in the metastatic and non‐metastatic disease subgroups, but no significant difference was seen in the lymphoma subgroup.…”
Section: Discussionsupporting
confidence: 86%
“…Our study reinforces the findings from a variety of clinical settings that LMWH prophylaxis reduces the proportion of patients with a significant bleeding event when compared with UFH and has a reduced rate of HIT . The significant reduction in bleeding may be because of the more consistent pharmacokinetic and dynamic properties demonstrated by LMWHs when compared with UFH . Our secondary analysis showed approximately a 2% significant reduction in significant bleeding in the metastatic and non‐metastatic disease subgroups, but no significant difference was seen in the lymphoma subgroup.…”
Section: Discussionsupporting
confidence: 86%
“…Trial characteristics are presented in Table 1. Most of these studies (10 observational studies and two RCTs) tested the effects of different dosages of enoxaparin [15][16][17][18][19][20][21][22][23][24][25][26], whereas four observational studies assessed dalteparin [27][28][29][30], and one each tested certoparin [31] and nadroparin [32]. No studies testing tinzaparin were identified.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of the studies according to the Down and Black score is shown in Table 2. The median total score (interquartile range, IQR) was 19 [15][16][17][18][19][20]…”
Section: Resultsmentioning
confidence: 99%
“…heparin, 1 although the anticoagulant effect of heparin is immediate. It takes 3 h for the peak anti-factor Xa (anti-FXa) plasma activity of enoxaparin, 46 yet the ASRA recommended a 2 h interval between catheter removal and subsequent redose. These recommendations on heparin and enoxaparin have been followed in thousands of patients with no reports of spinal haematoma, although this might represent underreporting and not proof of safety of the guidelines.…”
Section: Resumption Of Drug After Neuraxial Injection or Removal Of Ementioning
confidence: 99%